1970
DOI: 10.3329/jbs.v18i0.8767
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of genetic variability, correlation and path association in rice (<i>oryza sativa</i> l.)

Abstract: Context: Direct selection based on crop yields is often a paradox in breeding programmes because yield is a complex polygenically inherited character, influenced by its component traits. Objectives:The present research work was taken up to assess genetic variability, phenotypic and genotypic associations between various components of grain yield to provide basis for selection and yield improvement in rice. Materials and Methods:Correlation coefficient and path association are used to find out the degree (stren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 13 publications
14
15
0
Order By: Relevance
“…On the contrary, non-significant association was noticed for grain yield with days to 50 per cent flowering, plant height, panicle length and 1000-grain weight. The findings are in consonance with the reports of Yadav et al (2010).…”
Section: Resultssupporting
confidence: 92%
“…On the contrary, non-significant association was noticed for grain yield with days to 50 per cent flowering, plant height, panicle length and 1000-grain weight. The findings are in consonance with the reports of Yadav et al (2010).…”
Section: Resultssupporting
confidence: 92%
“…Similar significant result was found in case of BR28 (Table 1). Yield was significantly and positively associated with panicle length (Yadav et al 2010). We also found that flag leaf length was positively associated with panicle length, thereby indicating associated with grain yield.…”
Section: Discussionsupporting
confidence: 50%
“…This indicated that simultaneous selection of all these characters was important for yield improvement. Similar kind of association was revealed by Satish Chandra et al, (2009), Nandan andSweta Singh (2010) for days to flowering, Madhavilatha (2002) for days to maturity, Nandan and Sweta Singh (2010) and Ratna et al, (2015) for plant height, Idris and Mohamed (2013) for number of tillers per plant, Eswara reddy et al, (2013), Rahman et al,(2014) for panicle length, Yadav et al, (2010) for number of grains per panicle, Reddy et al, (1997), Madhavilatha et al, (2005) for kernel length and L/B ratio (Table 3).…”
Section: Resultsmentioning
confidence: 60%